Low Ability of Great Tits to Discriminate Similarly Inconspicuous Edible and Inedible Prey. (February 2016) - Karlíková, Zuzana; Veselý, Petr; Beránková, Jana; Fuchs, Roman
Abstract: Numerous studies have shown warning coloration to facilitate the discrimination of edible and inedible prey. However, inedible insect species may possess cryptic coloration as well. It has been shown that some other visual features (especially characteristic body shape) are sufficient for the recognition of some insect taxa (e.g. ladybirds, ants, wasps). We tested the ability of wild‐caught great tits ( Parus major ) to discriminate between the identically coloured edible (roach – Blaptica dubia ) and the inedible (firebug – Pyrrhocoris apterus ) as prey according to subtle peripheral visual traits (shape of legs and antennae, body posture, and means of locomotion). Both prey species were offered either simultaneously or alternately. The ability of the birds to learn was tested by means of fourteen trial repetitions in two sessions. In general, great tits were not able to learn to discriminate between firebugs and roaches by subtle shape cues alone during the two sessions. However, multivariate analysis of individual bird behaviour showed that they adopted one of three different attitudes to the presented prey. Most of the birds never attacked any or always attacked both prey. In addition, a small proportion of the birds was able to discriminate between the two prey types and attacked only roaches. Nevertheless, firebugs survived most of the attacks, which suggests that in case of chemically protected prey, the evolution of conspicuous coloration is not always the best/only option.